THE EFFECTS OF SMALL AMOUNTS OF H2O, CO2 AND NA2O ON THE PARTIAL MELTING OF SPINEL LHERZOLITE IN THE SYSTEM CAO-MGO-AL2O3-SIO2 ± H2O ± CO2 ± NA2O AT 1·1GPA - Liu X.; O'Neill H.St.C.; Berry A.J. (My University, 2006)
The effects of small amounts of H2O (<4wt % in the melt) on multiply saturated partial melting of spinel lherzolite system cao-mgo-al2O3-SiO2 ± Na2O ± CO2 have been determined at 1·1GPa in the piston-cylinder apparatus. Electron microprobe analysis and Fourier transform infrared spectroscopy were used to analyse the experimental products. The effects of H2O are to decrease the melting temperature by 45°C per wt % H2O in the melt, to increase the Al2O3 of the melts, decrease MgO and CaO, and leave SiO2 approximately constant, with melts changing from olivine- to quartz-normative. The effects of CO2 are insignificant at zero H2O, but become noticeable as H2O increases, tending to counteract the H2O. The interaction between H2O and CO2 causes the solubility of CO2 at vapour saturation to increase with increasing H2O, for small amounts of H2O. Neglect of the influence of CO2 in some previous studies on the hydrous partial melting of natural peridotite may explain apparent inconsistencies between the results. The effect of small amounts of H2O on multiply saturated melt compositions at 1·1GPa is similar to that of K2O, i.e. increasing H2O or K2O leads to quartz-normative compositions, but increasing Na2O produces an almost opposite trend, towards nepheline-normative compositions. © The Author 2005. Published by Oxford University Press. All rights reserved.
Keywords: CO2; FTIR; H2O; HYDROUS PARTIAL MELTING; MANTLE MELTING; SPINEL LHERZOLITE; SYSTEM CAO-MGO-AL2O3-SIO2 ± H2O ± CO2 ± NA2O